Development of an open-architecture temperature data logger for hydro-distillation agarwood oil extractor - Mohd Haslizam, Abdullah (2021)
Microcontroller based data logger system recently emerged as a powerful, flexible and cost-effective measurement solution to many innovative field applications in environmental monitoring, agriculture and solar energy. Real-time temperature is vital to provide discrete knowledge in the process of distillation as it involves mixture boiling, evaporation and condensation at the difference in liquid phases. The development of a data logger namely OCTATherm for use in the Agarwood extraction industry is realized by designing an electronic enclosure to protect an Arduino-based microcontroller system that can acquire eight (8) thermocouples readings for monitoring the hydro-distillation process. The accuracy and reliability of the data logger have been evaluated by assessing the hydro-distillation (HD) process on a laboratory scale by comparing its performance to the commercial data logger (HOBO UX120). Finally, the assessment in the industry with multi-boiler operate simultaneously shows that real-time monitoring of the temperature measurements at critical points of the conventional HD system can improve the yield of the extracted Agarwood essential oil by three (3) times higher from 0.027% to 0.101%. The implementation of real-time thermal management technology in the HD system in the Agarwood essential oil production industry is therefore of great importance. This developed data logger is significant to produce a real-time data acquisition and monitoring platform of temperature measurement, which aims to facilitate agriculture industry process monitoring as well as academic research purpose in another area. The open-architecture based system design is also highlighted in which provides future upgrades of expansion and extension features of the data logger.